Nanotoxicity in Physics Education: Electrochemical Synthesis of Carbon Dots and Their Effects on Mung Beans - Bao Nguyen Quach Nguyen; Quang Ngo Khoa; Hai Phung Viet; Siti Zulaikha Ngah Demon (Jurnal Pendidikan Fisika Indonesia, 2025)
This study introduces the toxicity of nanomaterials through a practical and accessible experiment. An electrochemical approach was employed to synthesize carbon dots (CDs) from graphite rods extracted from recycled batteries. The impact of CDs solutions on the growth of mung bean sprouts was then investigated as a representative model for nanotoxicity assessment. The results revealed significant differences in growth and development between control samples and those exposed to CDs. To evaluate the educational impact, an experiment was carried out with 25 undergraduate students divided into five groups. The activity helped students better understand the properties and risks of nanomaterials, while also developing their skills in data analysis and teamwork. Three surveys conducted before and after the lecture and experiment showed that students improved their knowledge of nanotechnology and their practical skills. This interdisciplinary experiment, integrating physics, chemistry, and biology, aligns with the Vietnamese Grade 10 Specialized Physics Study Module and undergraduate nanomaterial courses. Using recycled materials promotes sustainable practices and helps students connect theoretical knowledge with real-world applications, making learning more engaging and meaningful. It also provides a hands-on model for integrating nanoscience into STEM education in an accessible and practical way.